Impact of Negotiation Strategies on the Effectiveness of Communication: A Mediating Approach from Digital Public Relation [?????????????:???????????????] - Alhasani Y.R.M.; Muslim N.A.B. (Hunan University, 2023)
e-government; Public relations; 'current; Communication disciplines; Communication effectiveness; Digital public relation; Government organizations; Government services; Integrated management; Negotiation strategy; Social presence; Theoretical framework; Data acquisition